The Stage of the Estrus Cycle Is Critical for Interpretation of Female Mouse Social Interaction Behavior - Chari, Trishala; Griswold, Sophie; Andrews, Nick A.; Fagiolini, Michela (Frontiers in Behavioral Neuroscience, 2020)
Female animals in biomedical research have traditionally been excluded from research studies due to the perceived added complexity caused by the estrus cycle. However, given the importance of sex differences in a variety of neurological disorders, testing female mice is critical to identifying sex-linked effects in diseases. In order to determine the susceptibility of simple behaviors to hormonal fluctuations in the estrus cycle, we studied the effects of sex and the estrus cycle on a variety of behavioral tasks commonly used in mouse phenotyping laboratories. Male and female C57BL/6J mice were tested in a small battery of short duration tests and, immediately on completion of each test, females were classified using cytology of vaginal lavages as sexually-receptive (proestrus and estrus) or non-receptive (metestrus and diestrus). We showed that there was a significant difference in 3-chamber social interaction between female mice at different stages of their estrus cycle, with sexually-receptive mice showing no preferential interest in a novel female mouse compared with an empty chamber. Non-receptive female mice showed the same level of preference for a novel female mouse as male mice did for a novel male mouse. No differences between or within sexes were found for tests of anxiety (elevated plus maze, holeboard), working memory (novel object recognition) and motor learning (repeated tests on rotarod). We conclude that the stage of estrus cycle may impact social interaction between same-sex conspecifics, and does not impact performance in elevated plus maze, holeboard, novel object recognition, and rotarod.